Perceptions and Experiences of Marine Education Culture in the Marine Museum : A Comparative Study of Korea and Japan - Yang, Min-Ho; Kim, Joon-Hwan (Journal of Next-generation Convergence Information Services Technology, 2022)
This study compared the cases of Korea and Japan to examine the effect of the maritime education culture of maritime museums on the participation intention according to experiential factors. This study conducted an online survey on 280 people who visited the Korea National Maritime Museum in Busan, Korea, and the Kobe Maritime Museum in Japan. The survey showed that three of the five experiential factors proposed in this study (emotional, sensory, and relational) had a positive relationship with the respondents' intention to participate in both Korea and Japan. Moreover, the emotional factor had the most significant influence among the experiential factors affecting the intention to participate. The findings implied that maritime museums should improve not only their operational method of focusing on hosting information-oriented exhibitions but their emotional relationship with the viewers. This study provided theoretical and practical implications by conducting an empirical analysis of the effect of experiential factors on the intent to participate in maritime education culture through maritime museums. The findings of this study could also be applied to improve the quality of visitor experience and provide policy feedback. KCI Citation Count: 0